On Listening? : Listening (Anew) to an 80-Year-Old - Smit, Dirk J (Stellenbosch Theological Journal, 2022)
The article honours Denise Ackermann by seeking to understand why she named Karl Rahner as one of the theologians who influenced her own life and thought. Since the influence seems to flow from his Ignatian spirituality and practices of listening and discerning, the article attempts to understand the background, nature, and role of listening as spiritual practice in Rahner's life and work. In this process, the tension between transcendental and categorical thinking for him illuminates the tension between listening to her own feelings on the one hand and listening to the Man on the Borrowed Donkey on the other hand, manifest in her own life and work.